Decolonising the school experience through poetry to foreground truth-telling and cognitive justice. (16th February 2022) - Manathunga, Catherine; Davidow, Shelley; Williams, Paul; Willis, Alison; Raciti, Maria; Gilbey, Kathryn; Stanton, Sue; O'Chin, Hope; Chan, Alison
Abstract : While attempts to decolonise the school curriculum have been ongoing since the 1970s, the recent Black Lives Matter protests around the world have drawn urgent attention to the vast inequities faced by Black and First Nations peoples and people of colour. Decolonising education and other public institutions has become a front-line public concern around the world. In this article, we argue that poetry offers generative possibilities for the decolonisation of Australian high school (and university) curricula. Inspired by Aboriginal and Torres Strait Islander approaches to knowledge creation as intergenerational, iterative and intercultural, and by postcolonial and decolonial theories, we explore ways in which poetry events can begin decolonising and diversifying the school curriculum. We suggest that poetry creates spaces for deep listening with the heart ( dadirri ) that can promote truth-telling about colonial histories and the strengths, achievements and contributions of First Nations Australians. These decolonising efforts underpin the Wandiny (Gathering Together) – Listen With the Heart: Uniting Nations Through Poetry research that we discuss in this article. In these ways, we argue that decolonised curricula create the conditions for cognitive justice in schooling that is an important precursor to other forms of social justice, such as equality, diversity and inclusion.